Optimization parameter effects on the quality surface finish of the three-dimensional printing )3D printing) fused deposition modelling (FDM) process - Norazlin Saari (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
Fesed deposition modelling (FDM) is a process for developing rapid prototype (RD) objects according to namerically defined cross sectional geometry by depositing fused layer of material. This RP may used straigh to the application. Threrfore, This research has been done to optimize the best parameter towards better roughness on the surface, Plus, This research is to explor the influence of layer heigth, outline speed and extruder temperature with the surface roughness.